Effect of storage temperature on the quality of live mud crabs - Waritchon, N.; Yardrung, S.; Jiraporn, S. (International Journal of Agricultural Technology, 2022)
The chilling storage effect on the quality of live mud crabs was examined. The results showed that the chilling storage at 20ºC could decrease delayed loss of quality change with high remained glycogen (7.40±2.30 mg/100g), low accumulated lactate (9.75±0.12 mmol/kg) and 45.57±3.59 mgN/100g of VBN, while the pH decreased slightly average to 7.01±0.09. This condition is maintained muscle yield of 15.63±0.58% after 7 days. The total proximate compositions changed slightly during storage, the averaged between 78.10-79.10% of moisture content, 16.85-16.91% of protein, 0.10-0.22% of fat, and 1.4-1.54 % of ash on 4-7 days storage. Thus, result indicated that the 20ºC chilling storage can be benefit to the handling process and transport of mud crabs